Antecedents Relationship Commitment to Postpaid Service Products during the Covid 19 Pandemic - Nora Anisa Br Sinulingga; Risa Kartika Lubis; Harsyat Raq; Amanada Dwi Stephanie (Enrichment : Journal of Management, 2021)
During the Covid-19 Pandemic that occurred in the world, people communicated digitally, where Communication is one of the most important human needs. Along with advances in technology, nowadays consumers can easily communicate with other people using cell phones. The trend of cell phone usage itself is increasing. According to Gronross (2014) to build and maintain relationships with consumers, what is needed is to build good communication between companies and consumers. The results of this study are expected to be in the form of a model that can be used as a source of discussion, learning resources, learning resources and sources of inspiration for users of the "Kartu Halo" Postpaid Service. For that ServicePostpaid “Hello Card” constantly innovating products to satisfy their consumers, while the respondents in this study are service users Postpaid “Hello Card” in Medan, North Sumatra.